Price discovery in crude oil futures - Elder, John, author; Miao, Hong, author; Ramchander, Sanjay, author; Energy Economics, publisher (Colorado State University. Libraries, 2014)
This study examines price discovery among the two most prominent price benchmarks in the market for crude oil, WTI sweet crude and Brent sweet crude. Using data on the most active futures contracts measured at the one-second frequency, we find that WTI maintains a dominant role in price discovery relative to Brent, with an estimated information share in excess of 80%, over a sample from 2007 to 2012. Our analysis is robust to different decompositions of the sample, over pit-trading sessions and non-pit trading sessions, segmentation of days associated with major economic news releases, and data measured to the millisecond. We find no evidence that the dominant role of WTI in price discovery is diminished by the price spread between Brent that emerged in 2008.
Published as: Energy Economics, vol. 46, sup. 1, pp. s18-s27, December 2014, https://doi.org/10.1016/j.eneco.2014.09.012.
Keywords: crude oil futures; WTI; Brent; information sharing; inventory level; spread